Answer:
y = -0.2
General Formulas and Concepts:
Pre-Algebra
- Order of Operations: BPEMDAS
- Equality Properties
Step-by-step explanation:
Step 1: Define equation
[tex]\frac{3.6}{0.2(6y + 1)} =\frac{9}{0.5y}[/tex]
Step 2: Solve for y
- Distribute 0.2: [tex]\frac{3.6}{1.2y + 0.2} =\frac{9}{0.5y}[/tex]
- Cross-multiply: [tex]9(1.2y + 0.2) =3.6(0.5y)}[/tex]
- Distribute: [tex]10.8y + 1.8 =1.8y[/tex]
- Subtract 1.8y on both sides: [tex]9y + 1.8 =0[/tex]
- Subtract 1.8 on both sides: [tex]9y = -1.8[/tex]
- Divide both sides by 9: [tex]y = -0.2[/tex]
Step 3: Check
Plug in y to verify it's a solution.
- Substitute: [tex]\frac{3.6}{0.2(6(-0.2) + 1)} =\frac{9}{0.5(-0.2)}[/tex]
- Multiply: [tex]\frac{3.6}{0.2(-1.2 + 1)} =\frac{9}{-0.1}[/tex]
- Add: [tex]\frac{3.6}{0.2(-0.2)} =\frac{9}{-0.1}[/tex]
- Multiply: [tex]\frac{3.6}{-0.04} =\frac{9}{-0.1}[/tex]
- Divide: [tex]-90=-90[/tex]
Here we see that -90 does indeed equal -90. ∴ y = -0.2 is indeed a solution of the equation.